Renowned photographer donates refusenik archives to South Texas Jewish Archives - The Jewish Herald-Voice (The Jewish Herald-Voice, 2024)
On Monday, Oct. 21, the Joan and Stanford Alexander South Texas Jewish Archives hosted a special lecture featuring renowned photographer and activist Janice Rubin. Entitled “Refuseniks Revealed: Stories of Struggle and Hope from the Soviet Union,” the talk shed light on Rubin’s daring 1986 mission to document the lives of Soviet Jews denied permission to emigrate – a group known as “refuseniks.”
United States of America